Cities in Sight: Autonomous UAVs for 3D Maps without LiDAR - Chavarría-Zamora, Luis Alberto (2026)
In Costa Rica, urban topography faces the challenge of relying on expensive and unreliable LiDAR systems in adverse conditions such as fog or rain. To overcome these limitations, a low-cost autonomous UAV platform was developed. Equipped only with RGB cameras and an IMU, these UAVs generate three-dimensional urban maps. The proposal integrates hybrid monocular depth estimation techniques, combining self-supervised learning and knowledge transfer, with collaborative exploration algorithms based on swarms, Bézier curves, and pheromone modeling in Neo4J. After validating the design in simulations (PyBullet/Pygame) and real indoor flights, the system achieved depth accuracy of tens of centimeters, produced georeferenced point clouds, and allowed for the semantic segmentation of traffic and obstacles using ViT and YOLOv8. The results demonstrate that this approach offers a viable and economical alternative to traditional LiDAR, with the potential to deploy real-world swarms and optimize resources.